2019
DOI: 10.1002/ehf2.12517
|View full text |Cite
|
Sign up to set email alerts
|

Silent left ventricular apical ballooning and Takotsubo cardiomyopathy in an Australian intensive care unit

Abstract: Aims Recent reports have shown a high incidence of silent left ventricular apical ballooning (LVAB) in the intensive care unit (ICU) setting with potential implications for safe use of inotropes and vasopressors. We examined the incidence, predictors, and associated outcomes of LVAB in patients in a contemporary tertiary Australian ICU. Methods and resultsIn a prospective cohort study, patients were screened within 24 h of admission to the ICU and enrolled if they were deemed critically unwell based on mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Moreover, most patients who did undergo coronary angiography had normal coronary arteries, and patients with follow‐up echocardiogram had a rapid recovery of cardiac function, usually within days, which is not seen in myocardial infarction without coronary intervention. 27 In our study, we identified 12 patients (3%) with apical or midventricular hypokinesia, in concordance with typical Takotsubo, which is an incidence in agreement with other ICU‐oriented studies focusing on this subject, 14 , 15 , 28 although some studies have reported higher numbers. 17 …”
Section: Discussionsupporting
confidence: 90%
“…Moreover, most patients who did undergo coronary angiography had normal coronary arteries, and patients with follow‐up echocardiogram had a rapid recovery of cardiac function, usually within days, which is not seen in myocardial infarction without coronary intervention. 27 In our study, we identified 12 patients (3%) with apical or midventricular hypokinesia, in concordance with typical Takotsubo, which is an incidence in agreement with other ICU‐oriented studies focusing on this subject, 14 , 15 , 28 although some studies have reported higher numbers. 17 …”
Section: Discussionsupporting
confidence: 90%
“…Since the onset of TS is frequently associated with preceding stress from various sources, it appears reasonable that critically ill patients develop TS as a secondary disease. Indeed, the incidence of TS in critical care units in observational studies is substantial and higher than expected [95][96][97][98]. Therefore, TS should be suspected in patients with unexplained heart failure, hypotension, shock, arrhythmia, or troponin elevation, and dedicated echocardiography should be performed.…”
Section: Incidencementioning
confidence: 99%
“…The proportion of patients in our study with complications of systolic heart failure and cardiogenic shock, was 77.36% and 39.62%, respectively. A total of 86.79% of patients were given (7,8). The APACHE II score has been validated as an accurate predictor of clinical outcomes and mortality in critically ill patients (12).…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms or aetiologies may explain the occurrence of SC in ICU and are may be combined: catecholamine toxicity, psychological stress, neurological impairment, ischemia and left ventricular outflow track obstruction (6). Previous studies have reported that SC incidence in the ICU ranged from 1.5% to 5.6% (6)(7)(8). One study showed that >20% of patients admitted to the ICU displayed SC-like LV apical ballooning (9).…”
Section: Introductionmentioning
confidence: 99%